دراسة بعض الصفات المورفولوجية ومكونات الغلة لطرز فاصولياء الليما (Phaseolus lunatus L. ) المنتشرة بالزراعة المحلية - بوراس, متيادي; معلا, محمد; السعدي, محمد (Latakia University Journal -Biological Sciences Series, 2018)
أجريت الدراسة في مركز البحوث العلمية الزراعية في درعا (جنوب سورية) بهدف تقييم الصفات الاقتصادية (مكونات الغلة) والخصائص البيولوجية لأربعة طرز من فاصولياء الليما جُمعت من عدة مناطق في سورية. واستمرت لموسمين زراعيين متتالين ( 2003 و 2004). أظهرت النتائج وجود تنوع بين الطرز المدروسة بصفة لون الأزهار ( بيضاء, بنفسجية ) ولون البذور (بيضاء, بيضاء مع بقعة بنية عند السرة, بيضاء مخططة بالبني, بنية مخططة بالأبيض). فضلاً عن وجود تباين وراثي بينها لأغلب الصفات المدروسة ( طول الساق الرئيسية, طول القرن, عدد القرون على النبات, عدد البذور بالقرن, وزن الـ 1000 بذرة , إنتاجية النبات من البذور الجافة ) . كما أظهرت أيضاً وجود علاقة ارتباطية ايجابية بين الإنتاجية وكلاً من عدد البذور في القرن ( r = 0.66 ) وعدد القرون على النبات (r = 0.50) وطول الساق الرئيسية (r = 0.56 ) وعلاقة سلبية مع وزن الـ 1000 بذرة ( r = - 0.11 ) . يمكن الاعتماد على هذة العلاقة الارتباطية كمؤشر انتخابي selecting index . Four local genotypes of lima beans from various regions of Syria were evaluated for the most important biological characters, and economic traits (yield components), In Daraُa center for Agricultural Scientific Research during the seasons 2003 - 2004 . The study showed diversity in the color of flower (white, violet) and seed (white, white with brown hilum, white with brown stripes, brown with white stripes). The results showed significant genetic variation between genotypes by the most characters (length of main stem, length of pod, number of pods per plant, number of seeds per pod, weight of 1000 seeds, and dry seed yield of plant). The correlations between the yield and yield components were varied, it was a positive value between dry seed yield of plant and seeds per pod )r = 0.66 ) and with pods per plant )r = 0.50) and with length of main stem )r = 0.56), and it was a negative value with weight of 1000 seeds )r = - 0.11). The study recommended the use of correlations as a selection index.